Efficiency of one-on-one play situations of Polish football players and their opponents during European Championships in relation to the playing area, current result and match - Andrzej Szwarc; Christoph Kromke; Aleksander Stuła; Bartosz Dolański; Mateusz Sitek (Physical Education of Students, 2020)
Background and Study Aim. The aim of the study was to assess the effectiveness of players of the Polish national football team and their opponents in one-on-one situations (1-on-1) in 9 matches of the group stage of the three subsequent finals of the European Championships in the years 2008, 2012 and 2016.